Rethinking mass tourism: Professional discourses of contemporary mass tourism and destinations - Vilhelmiina Vainikka (Nordia Geographical Publications, 2015)
Mass tourism is a concept that has been used for decades in academic and public travel discussions, and thus it serves a purpose. Mass tourism is often used to refer to the early phases of air-based mass tourism since the 1960s, concerning the remarkable growth in tourist numbers, democratization of tourism, standardization of products and societal transformations. It is also used to emphasize certain motivations, behaviours and values in tourism that are seen as typical for mass tourism separating it from other contemporary or ‘alternative’ forms of tourism. This distinction frequently produces taken for granted or simplified categorizations both in tourism studies and in public discourses. Within tourism studies discussions about the conceptualization of mass tourism between different traditions have been almost non-existent. In this study, my interest is in the different ways mass tourism can be conceptualized. Tourism is now a larger phenomenon than ever and transformations have occurred in its production and consumption, demanding that the limits and possibilities of the concept of mass tourism need to be evaluated in new ways.